Seepage Analysis of Senggarang Coastal Embankment with Chemically-Stabilised Backfill - Roslan, Nurhakimi; Yahya, Nur Faezah; Chan Chee Ming; Salina Sani (Progress in Engineering Application and Technology, 2022)
One of the common problems faced at embankment is water seepage. In this study, seepage happened at the inland area which causing floods and disrupted agriculture in the surroundings area. The objectives of this research are to investigate the senggarang coastal embankment (SCE) seepage problem with a focus on the engineering properties of the backfill and to recommend the best chemical stabilization strategy for SCE seepage mitigation by using PLAXIS 8 software This study involved numerical simulation with the usage of the PLAXIS 8 software. Embankment was simulated using bedrock while the foundation of the embankment was treated and untreated silty clay. Data parameters were collected from previous study. Different water level was applied to see the changes of pore pressure distribution which lead to instability of the embankment. As water level increase, the total displacement increase. Therefore, in this study, the use of two chemical agents which are cement-CSP and lime-ZnO will be compared to determine which one is the best chemical agent that can solve the seepage problem at the embankment. As a result, after the outputs from the PLAXIS software for both chemical agents which are total displacement, effective stress, excess pore pressure, and seepage analysis were being compared, this study have identified that the cement-CSP was the best chemical agent that can stabilize the silty clay and reduce seepage problems at the embankment.